MACROECONOMIC AND BANK-SPECIFIC DETERMINANTS OF LOAN LOSS PROVISIONING IN INDONESIA - Suhartono Suhartono (Universitas Hayam Wuruk Perbanas, 2012)
This paper used Generalized-Linear Model (GLM) with the exposure time to examine the determinants ofcredit loss provisions in Indonesia's banking sector. The research was motivated by the hypothesis thatboth macro economic variables and bank - specific have an effect on the quality of loans and loan lossprovisions to cover risks. The results showed that loan losses could be explained primarily by a particularbank and macro economic variables. On asset size, the study found a positive relationship between the sizeof assets and loan loss provisions indicating that there is no benefit for the large banks of their managerialand technological advantages. Well-capitalized bank with a negative impact on loan loss provisions, thebank also showed that the capitalized ones take less credit risk. It appears clear that inefficient banks torisk further demonstrate the validity of the hypothesis of poor management. Using the profitability/ReturnOn Average Assets (ROAA), it was found that there is a negative relationship implying that profitable banksave lower credit risk and also support the hypothesis that good management to take the risk is lower. Onthe impact of the price index, it was found negative showing higher inflation reduces loan loss provisions.In terms of economic growth/Growth Development (GD), the results provide further evidence that economicgrowth reduces credit risk and that this provides further support of procyclicality in credit markets.